"Hanuman’s Journey to Lolland" By Andrey Ivanov as a Provocation of the Modern Reader (Based on the Postulates of Reception Aesthetics) - Шалкине, Александра (Literatūra, 2017)
A brief summary of the main concepts of Jauss’s aesthetic reception theory is followed by an analysis of the novel Haluman’s Journey to Lolland by Andrey Ivanov. By provoking the reader, the author constantly attempts to move their horizons of expectation. Ivanov creates a “novel without a plot” and calls it a travelogue, despite the fact that the storyline does not involve an actual journey. By parodying the chivalric romance and the subsequent jester’s romance, the author actualizes the aspects that are import to him and explains the characters’ “philosophy of non-resistance.” Ivanov’s novel is set in a Danish refugee camp, which acts as a parody of the 20th century European social and economic structure. Ivanov’s provocative anticosmopolitanism makes the reader adopt a new perspective on the European policy of refugee integration. Furthermore, the author flirts with the dream of the Soviet people to move to the US, the interpretation of Buddhism and religious postulates, the traditional notion of a respectable life goal and other aspects. The second part of the article concerns the system of characters. First of all, the toponym “Lolland” is analyzed; then, the names of the main characters (e.g., Hanuman, Eugene, Yevgeny and other variants) are examined. At the same time, a brief analysis of intertextual relationships demonstrates how Ivanov adopts ethical questions raised in the works of classical writers, such as Alexander Pushkin, and transfers them to the 20th century or attempts to find an answer in the modern world with its moral principles. In addition, intertextual relationships with Russian folklore, works by N. Karamzin as well as I. Ilf and E. Petrov are described. The 20th century issue of a lost motherland is also discussed. In conclusion, it can be argued that by provoking the reader in various ways, the author focuses on people of different ages and makes his novel comprehensible and attractive for people of different generations.ANDREJAUS IVANOVO ROMANAS „HANUMANO KELIONĖ Į LOLANDĄ“ KAIP ŠIUOLAIKINIO SKAITYTOJO PROVOKACIJA (PAGAL ESTETINIO SUVOKIMO TEORIJĄ)Trumpai apibendrinę pagrindinius Jausso estetinio suvokimo teorijos terminus, pereiname prie Andrejaus Ivanovo romano „Hanumano kelionė į Lolandą“ analizės. Provokuodamas skaitytoją, autorius nuolat bando sujudinti jo lūkesčių horizontus. Ivanovas kuria „romaną be siužeto“, pavadina jį „kelionių knyga“, nors jame nėra jokios kelionės. Parodijuodamas riterių romaną ir vėlesnį juokdarių romaną, autorius aktualizuoja jam reikalingus aspektus ir aiškina veikėjų „nieko nedarymo filosofiją“. Ivanovo romane aprašyta pabėgėlių stovykla Danijoje – XX a. Europos modelio parodija. Provokuojantis Ivanovo antikosmopolitizmas priverčia skaitytoją kitaip pažvelgti į Europos pabėgėlių integracijos politiką. Be to, autorius žaidžia su visų Sovietų Sąjungos žmonių svajone išvažiuoti į Ameriką, budizmo supratimu ir religijos postulatais, tradiciniu garbingu gyvenimo tikslu ir kitais aspektais. Antroje straipsnio dalyje analizuojama veikėjų sistema. Iš pradžių nagrinėjamas Lolando vietovės pavadinimas, po to – pagrindinių veikėjų vardai (Hanumanas, Judžinas, Eugenijus ir kiti jų variantai). Tuo pat metu trumpa intertekstualinių ryšių analizė parodo, kaip Ivanovas perima klasikinių rašytojų (pavyzdžiui, Aleksandro Puškino) kūriniuose užduotus etinius klausimus, perkelia juos į XX amžių ar mėgina rasti atsakymą šiuolaikiniame pasaulyje, jo moralinėje sistemoje ir principuose. Taip pat analizuojami intertekstualiniai ryšiai su I. Ilfo ir E. Petrovo, N. Karamzino kūriniais bei rusų tautosaka. Straipsnyje taip pat kalbama apie prarastos tėvynės problemą XX a. žmogaus pasaulėžiūroje. Apibendrinant galima teigti, kad „Kelionės“ autorius provokuodamas skaitytoją įvairiais būdais orientuojasi į skirtingo amžiaus žmones ir „daro“ savo tekstą suprantamą ir įdomų įvairių kartų atstovams.
Keywords: horizon of expectations; provocation; anti-cosmopolitanism; journey; parody; system of characters.